Early detection of myocardial dysfunction in poorly treated pediatric thalassemia children and adolescents: Two Saudi centers experience - Ibrahim, Mohamed H. (Ann Med Surg (Lond), 2016)
BACKGROUND & OBJECTIVE: Cardiac complications are among the most serious complications in Beta Thalassemia Major Patients. Our aim was to evaluate the value of tissue Doppler imaging (TDI) for early detection of myocardial dysfunction in pediatric and adolescent patients with B-TM before development of overt heart failure or cardiomyopathy. PATIENTS AND METHODS: 100 thalassemic patients below 18 years old and 100 healthy, age & sex matched controls were enrolled in our case-control study. Cases were selected from those attending outpatient clinics and inpatient wards, King Abdulaziz University hospital and Alhada Armed Forces Hospital, Saudi Arabia, between January 2014 and January 2015. They were subjected to echo-Doppler examination for both septal and lateral walls of the basal mitral and tricuspid annuli assessing the systolic myocardial velocity (S wave), early diastolic myocardial velocity (Ea wave) and late diastolic myocardial velocity (Aa wave). RESULTS: Patients with thalassemia have RV and LV dysfunction on the basis of abnormal TDI derived myocardial velocities. There was a statistically significant differences between patients and controls regarding (Aa) and (S) of the septal wall of the basal mitral annulus and (Ea) of the lateral wall of the mitral annulus. Also patients with thalassemia have significantly higher (S) of the basal tricuspid annulus. These abnormalities were not detected by conventional echo-Doppler. CONCLUSION: Clinically asymptomatic thalassemic children and adolescents who had normal global functions by conventional echo-Doppler were found to have abnormal left ventricular and right ventricular dysfunctions detected by TDI. TDI is superior to Echo-Doppler in detection of early myocardial damage in asymptomatic thalassaemic patients.